Job Characteristics and Creative Performance in Indonesian MSMEs: The Serial Mediation of Psychological Well Being and Creative Process Engagement - Fika Rahmanita; Ade Banani; Ratno Purnomo (Fundamental and Applied Management Journal, 2026)
In the dynamic Indonesian MSME sector, where innovation is crucial for competitive survival yet constrained by limited resources, job design remains a key lever for enhancing employee creativity. This study examines how job characteristics affect creative performance, with psychological well‑being and creative process engagement acting as serial mediators. The research aims to clarify the psychological and process mechanisms through which job characteristics translate into creative performance in Indonesian MSMEs. A cross‑sectional, multi‑source survey was conducted among 257 MSME employees across major innovation hubs in Indonesia. Data were analyzed using partial least squares structural equation modeling (PLS‑SEM). The results show that job characteristics positively influence psychological well‑being, creative process engagement, and creative performance directly. Psychological well‑being further strengthens creative process engagement, which in turn enhances creative performance. Parallel and serial mediation analyses confirm that the serial pathway job characteristics, psychological well‑being, creative process engagement, and creative performance are the dominant mechanisms, explaining up to 85.9% of the variance in creative performance. The findings contribute to management theory by integrating the Job Characteristics Model, Self‑Determination Theory, creative process engagement, and the Componential Theory of Creativity, thereby unpacking how job characteristics are transformed into creative excellence in resource‑constrained MSME environments. Practically, the study provides Indonesian MSME managers with evidence‑based guidelines for job enrichment, emphasizing skill variety, autonomy, and feedback to strengthen psychological well‑being, activate creative process engagement, and exploit employee creativity as a sustainable competitive advantage.